2014
DOI: 10.1039/c3tb21300e
|View full text |Cite
|
Sign up to set email alerts
|

Site specific immobilization of a potent antimicrobial peptide onto silicone catheters: evaluation against urinary tract infection pathogens

Abstract: Bacterial colonization of urinary catheters is a common problem leading to Catheter Associated Urinary Tract Infections (CAUTIs) in patients, which result in high treatment costs and associated complications. Due to the advantages of antimicrobial peptides (AMPs) compared to most other antimicrobial molecules, an increasing number of AMP-coated surfaces is being developed but their efficacy is hindered by suboptimal coating methods and loss of peptide activity upon surface tethering. This study aims to address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 53 publications
3
65
0
Order By: Relevance
“…Coating of a 13mer GL13K peptide also made the titanium surface antibiofilm [49]. Likewise, immobilization of a 15mer lasioglossin LL-III to silicone catheters conferred antibiofilm ability to the device [50]. Recently, Xavier et al showed that synthetic lactams could also inhibit the growth of Streptococcus mutans on titanium [51].…”
Section: Discussionmentioning
confidence: 99%
“…Coating of a 13mer GL13K peptide also made the titanium surface antibiofilm [49]. Likewise, immobilization of a 15mer lasioglossin LL-III to silicone catheters conferred antibiofilm ability to the device [50]. Recently, Xavier et al showed that synthetic lactams could also inhibit the growth of Streptococcus mutans on titanium [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, some of the issues with AMPs are their suboptimal coating properties, potential toxicity, pH sensitivity and high cost of synthesis [10]. Some of these issues have been addressed recently, where Mishra et al immobilized peptides on silicone catheters [122]. A sulfhydryl coupling was used to immobilize the antimicrobial peptide, Lasio-III on the silicone urinary catheter.…”
Section: Antimicrobial Urinary Catheter Coating Agents/materials Imentioning
confidence: 99%
“…Moreover, such sequences could be more suitable for chemical grafting onto materials of medical interest. It is worth to note that immobilized peptides often show a significantly reduced cytotoxic potential when compared to their soluble counterparts [33,47,63]. In this respect, ongoing studies are aimed at the identification of shorter peptide analogs and derivatives most suitable for chemical immobilization on biomedical materials.…”
Section: Discussionmentioning
confidence: 99%